Reestructuración del sistema de tratamiento de agua potable de la sede Usme de la Universidad Antonio Nariño (2021)
Water is one of the most important vital elements for our current society, for this reason it is necessary to offer the resource to have an adequate treatment of it; since poor water quality or inadequate treatment can be the precursors of water-borne diseases (HAD) in humans; These diseases are transmitted by bacteria, viruses, helminth eggs and protozoa contained in raw water and there are various types of these diseases such as: gastroenteritis, diarrheal diseases, arsenicosis, fluorosis, schistomiasis, helminthiasis, malaria, dengue, legionellosis, hepatitis A and E, poliomyelitis, thyroid fever, meningitis, among others. For the development of the research work, a physicochemical and microbiological analysis of the water sample from the Usme headquarters of the UAN was carried out, identifying variables such as the presence of fecal and total coliforms, which do not comply with Resolution 2115 of 2007, determining from this It is important to take preventive measures against diseases that are transmitted by this means, for this reason it is decided to conceptually propose the best cost-benefit option for a drinking water treatment plant that meets the needs of the type of water and institutional population